2018
DOI: 10.1007/s12223-018-0624-1
|View full text |Cite
|
Sign up to set email alerts
|

Suitability and setup of next-generation sequencing-based method for taxonomic characterization of aquatic microbial biofilm

Abstract: A robust and widely applicable method for sampling of aquatic microbial biofilm and further sample processing is presented. The method is based on next-generation sequencing of V4-V5 variable regions of 16S rRNA gene and further statistical analysis of sequencing data, which could be useful not only to investigate taxonomic composition of biofilm bacterial consortia but also to assess aquatic ecosystem health. Five artificial materials commonly used for biofilm growth (glass, stainless steel, aluminum, polypro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The V4‐V5 region of the 16S rRNA gene has been one of the most broadly used variable regions in studies examining environmental biofilms on artificial surfaces (e.g., Bakal et al, 2018 ; Li et al, 2017 ; Pereira et al, 2017 ), while 515F/926R has been suggested as a primer set that increases percentage detection of various prokaryotic taxa (Pollet et al, 2018 ) as well as been the most effective region in minimizing overestimation due to intragenomic heterogeneity (Sun et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The V4‐V5 region of the 16S rRNA gene has been one of the most broadly used variable regions in studies examining environmental biofilms on artificial surfaces (e.g., Bakal et al, 2018 ; Li et al, 2017 ; Pereira et al, 2017 ), while 515F/926R has been suggested as a primer set that increases percentage detection of various prokaryotic taxa (Pollet et al, 2018 ) as well as been the most effective region in minimizing overestimation due to intragenomic heterogeneity (Sun et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The V4-V5 region of the 16S rRNA gene has been one of the most broadly used variable regions in studies examining environmental biofilms on artificial surfaces (e.g. Li et al ., 2017; Pereira et al ., 2017; Bakal et al ., 2018), while 515F/926R has been suggested as a primer set that increases percentage detection of various prokaryotic taxa (Pollet et al ., 2018) as well as been the most effective region in minimising overestimation due to intragenomic heterogeneity (Sun et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Submerged plants are planted in the submerged oxygen pond, which can use the photosynthesis and respiration of submerged plants to build an ecological food chain system and realize the deep purification of water quality. Pebbles are preferably paved in the multi-stage falling water oxygenation ecological ditch, and they lay in a single ecological ditch facilitate the propagation and growth of biofilm on pebbles and promote the occurrence of nitrification reaction [25][26][27]. Aquatic plants are planted at the junction of the two ecological ditches and where the water flow is slow to form a multi-functional water drop oxygenation and ecological ditch, strengthen the purification effect, beautify the environment and increase economic benefits.…”
Section: Removal Mechanism Analysismentioning
confidence: 99%